Rethinking Revolutions from 1905 to 1934
XX, 372 p. 2 illus., 1 illus. in color.
Keywords: This edited collection offers a timely and original perspective on the many upheavals and revolutions that broke out across the world during the earlytwentieth century. With previous research tending to confine revolutions within national borders, this book sets out to place them within a broader global sphere of thought and action. The authors explore the time phase between the Russian Revolution of 1905 and the Asturian Revolution of 1934, including cases from South Africa, Australia, China, the Middle East and Latin America. Providing insights from leading scholars in the field, this collection highlights the interconnectedness and transnationalism of upheavals and revolutions, offering a new approach which integrates political, social and cultural history. Chapter 8 is available open access under a Creative Commons Attribution 4.0 International License via Link.springer.com .